Fruit growing - Dixon, R. T. (The Commonwealth and International Library : Rural and Environmental Studies Division, 1966)
Fruit Growing studies fruits, including its characterization and kinds; essential agricultural, horticultural, and silvicultural practices; and consumption. This book first qualifies what fruit is and then discusses some fruits such as berries and bush fruits. Various practices in growing, maintaining, and harvesting fruits are then examined, including cutting, layering, pruning, stooling, grafting, and pruning. How to plan and maintain a fruit garden is also explained. The latter part concerns itself with fruit storage, preparation, and record keeping. This text is a very helpful guide for th.